Ankle fractures in patients over age 55 years: Predictors of functional outcome. Issue 3 (27th September 2020) - Simske, Natasha M.; Benedick, Alex; Audet, Megan A.; Vallier, Heather A.
Abstract: Objectives: To identify predictors of functional outcomes following treatment of ankle fracture in patients 55 years or older. Setting: Level 1 Trauma Center. Patients/participants: Four hundred twenty-nine patients with torsional ankle fractures (44A-C): 233 patients (54%) were ages 55 to 64, 25% were between the ages 65 and 74; 21% were 75 years or older. Intervention: Operative or nonoperative management of ankle fracture. Main outcome measure: Early complications were assessed for all patients after minimum of 6 months, and functional outcome scores as assessed by the Foot Function Index (FFI; n = 166, 39%) and Short Musculoskeletal Function Assessment (SMFA; n = 168, 39%) after median 57 months follow-up. Results: Surgical management was elected in 67% of patients. Nonoperative management became more common with advancing age and was associated with fewer unplanned operations (12% vs 3%, P < .01) and complications (21% vs 13%, P = .07). African American race was associated with worse pain on the FFI ( P = .002) and BMI was associated with worse (higher) scores on all categories of the FFI and SMFA (all P < .05). Diabetes, neuropathy, and mental illness were also predictive of worse scores on various categories of both surveys. Assistive device use or nonambulatory status at the time of injury was associated with worse disability/dysfunction, activity, and mobility scores on both the FFI and SMFA (all P > 15, P < .05). Sex, Hispanic ethnicity, tobacco use, open fracture, dislocation, fracture pattern, and operative management were not independent predictors in this regression model. Conclusions: Baseline health and ambulatory capacity at injury were more predictive of outcomes following ankle fracture than were fracture characteristics or type of treatment.